The Better Life Index Youth: What can it contribute to an evidence-based youth policy? - Gärtner, Kathrin; Ponocny, Ivo (Momentum Quarterly, 2018)
For the 7th report on the situation of youth in Austria, a Better Life Index Youth was constructed involving the participation of youth experts and young people themselves with the aim to measure youth well-being in Austria. The Better Life Index Youth is a sum index based on data from EU-SILC 2013 and consisting of ten sub-indices: material living conditions, work, health, education, social relations, leisure, safety, quality of societal organisation, housing and subjective well-being. The index is especially suitable to analyse group differences in different domains and therefore to identify risk populations. It could be shown, for example, that young people living in rural areas generally reach higher values than young people living in the cities. However, the BLI Youth is currently no suitable measure to compare different life domains, to show developments over time or to enable international comparisons. An index which can serve these needs would at least partly have to be based on other data.